Alternative Learning Plots: A Narrative Inquiry into Teachers’ Competence Building in the Classroom - Nagy-Váci, Krisztina (Working Papers in Language Pedagogy, 2013)
The present study aims at exploring secondary school language teachers’ ways of learning teaching skills, that is, the learning plots which are constructed through narrating small stories about critical incidents in the classroom. As part of a greater grounded theory study, six teachers have been interviewed to enrich existing findings on teachers’ competence building. In the research process, four alternative teacher responses have been identified through constant comparison and coding procedures. These are the avoidance of competence building, experimenting with competences, delaying competence building and persevering with one’s own beliefs. The analysis intends to complement our understanding of teacher development through classroom experience.